Psychology of Communication : course of lectures. Lecture 1. Topic: Basic principles of communication - Луценко, Олена Львівна; Lutsenko, O. L. (Харків : Харківський національний університет імені В.Н. Каразіна, 2018)
Topic 1. Communicational competence: Educational goals. Course structure. Methods of assessing the acquisition of the course. Basic definitions. Topic 2. Types of communication. Characteristics of communication: Verbal and non-verbal. Formal and informal. Communicational principles. Main characteristics of communication: participants, messages, context, channels, interference, feedback. Honest and manipulative communication.
Keywords: communication; psychology; medical; healh care